Complement Factor H Levels Associate With Plasmodium falciparum Malaria Susceptibility and Severity. (20th July 2018) - van Beek, Anna E; Sarr, Isatou; Correa, Simon; Nwakanma, Davis; Brouwer, Mieke C; Wouters, Diana; Secka, Fatou; Anderson, Suzanne T B; Conway, David J; Walther, Michael; Levin, Michael; Kuijpers, Taco W; et al.
Abstract: Background: Plasmodium falciparum may evade complement-mediated host defense by hijacking complement Factor H (FH), a negative regulator of the alternative complement pathway. Plasma levels of FH vary between individuals and may therefore influence malaria susceptibility and severity. Methods: We measured convalescent FH plasma levels in 149 Gambian children who had recovered from uncomplicated or severe P. falciparum malaria and in 173 healthy control children. We compared FH plasma levels between children with malaria and healthy controls, and between children with severe (n = 82) and uncomplicated malaria (n = 67). We determined associations between FH plasma levels and laboratory features of severity and used multivariate analyses to examine associations with FH when accounting for other determinants of severity. Results: FH plasma levels differed significantly between controls, uncomplicated malaria cases, and severe malaria cases (mean [95% confidence interval], 257 [250 to 264], 288 [268 to 309], and 328 [313 to 344] µg/mL, respectively; analysis of variance P < .0001). FH plasma levels correlated with severity biomarkers, including lactate, parasitemia, and parasite density, but did not correlate with levels of PfHRP2, which represent the total body parasite load. Associations with severity and lactate remained significant when adjusting for age and parasite load. Conclusions: Natural variation in FH plasma levels is associated with malaria susceptibility and severity. A prospective study will be needed to strengthen evidence for causation, but our findings suggest that interfering with FH binding by P. falciparum might be useful for malaria prevention or treatment.